Cartilla ilustrativa para cuidadores sobre el manejo de higiene oral de pacientes con poca o nula movilidad (2021)
This investigative work has been carried out in order to determine the relevance of a illustrative booklet on oral health through the assessment of professional caregivers with experience in caring for patients with little or no mobility.